A Walk on the Wild Side: 'Predatory' Journals and Information Asymmetries in Scientific Evaluations - Manuel F. Bagues; Mauro Sylos-Labini; Natalia Zinovyeva (Institute of Labor Economics (IZA), 2017)
In recent years the academic world has experienced a mushrooming of journals that falsely pretend to be legitimate academic outlets. We study this phenomenon using information from 46,000 researchers seeking promotion in Italian academia. About 5% of them have published in journals included in the blacklist of 'potential, possible, or probable predatory journals' elaborated by the scholarly librarian Jeffrey Beall. Data from a survey that we conducted among these researchers confirms that at least one third of these journals do not provide peer review or they engage in some other type of irregular editorial practice. We identify two factors that may have spurred publications in dubious journals. First, some of these journals have managed to be included in citation indexes such as Scopus that many institutions consider as a guarantee of quality. Second, we show that authors who publish in these journals are more likely to receive a positive evaluation when (randomly selected) scientific evaluators lack research expertise. Overall, our analysis suggests that the proliferation of 'predatory' journals may reflect the existence of severe information asymmetries in scientific evaluations.
Keywords: I23; 330; scientific misconduct; academic evaluations